2019
DOI: 10.1186/s40643-019-0246-8
|View full text |Cite
|
Sign up to set email alerts
|

The antimicrobial effects and mechanism of ε-poly-lysine against Staphylococcus aureus

Abstract: Background: As a natural antibacterial cationic peptide, ε-poly-l-lysine (ε-PL) is applied as a food preservative. However, the mechanism of ε-PL against Staphylococcus aureus (S. aureus) has not been elucidated. Especially, its antimicrobial mechanism at the metabolomics has not been yet thoroughly described. Results: This work aimed at clarifying the antibacterial activity and mechanism of ε-PL against S. aureus. Effects of ε-PL with different concentration on cell morphology, cell wall, and membrane integri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
66
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 88 publications
(72 citation statements)
references
References 31 publications
5
66
1
Order By: Relevance
“…(Poly-ε-lysine) (ε-PL) (PLS) is a naturally created antibacterial homopolypeptide of 25–30 L-lysine residues that is stable in basic and acidic environments as well as at high temperatures [ 21 , 22 ]. Moreover, it is biodegradable, water-soluble, edible, non-toxic, and has broad-spectrum antibacterial properties [ 21 , 23 ]. Polylysine has therefore recently been incorporated into resin composites with remineralising agents [ 22 , 24 ].…”
Section: Introductionmentioning
confidence: 99%
“…(Poly-ε-lysine) (ε-PL) (PLS) is a naturally created antibacterial homopolypeptide of 25–30 L-lysine residues that is stable in basic and acidic environments as well as at high temperatures [ 21 , 22 ]. Moreover, it is biodegradable, water-soluble, edible, non-toxic, and has broad-spectrum antibacterial properties [ 21 , 23 ]. Polylysine has therefore recently been incorporated into resin composites with remineralising agents [ 22 , 24 ].…”
Section: Introductionmentioning
confidence: 99%
“…The predominance of red-fluorescent cells confirms that the growth inhibition is due to the bactericidal effect of the peptide and not only a bacteriostatic effect. In order to study the effects of EPL on S. aureus cell membrane, Tan et al showed that after EPL treatment there was a remarkable increase in fluorescence intensity measured by propidium iodide assay indicating an increase in cell membrane permeability 37 . When S. aureus cells were treated with 250 μg/ml of EPL, the cells appeared collapsed, lysed and with non-integral cell morphology 37 .…”
Section: Discussionmentioning
confidence: 99%
“…In order to study the effects of EPL on S. aureus cell membrane, Tan et al showed that after EPL treatment there was a remarkable increase in fluorescence intensity measured by propidium iodide assay indicating an increase in cell membrane permeability 37 . When S. aureus cells were treated with 250 μg/ml of EPL, the cells appeared collapsed, lysed and with non-integral cell morphology 37 . Similar results were obtained after treating E. coli cells with 50 μg/ml of EPL for 4 h. They observed that the external membrane and cytoplasm were damaged, surrounded by cell debris and with wrinkled appearance 25 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…26 The mechanism of action of pɛK previously described involves disruption of the cell membrane and the cell wall. 27,28 Cross-linking pɛK with a dicarboxylic acid using carbodiimide chemistry results in a transparent hydrogel with excellent mechanical properties that can be cast into a CL and is nontoxic to corneal epithelial cells. 26 PɛK hydrogels, therefore, have the potential to be used as a bandage CL.…”
mentioning
confidence: 99%